1, 25‐Dihydroxyvitamin D3 suppresses CD4+ T‐cell effector functionality by inhibition of glycolysis. Issue 3 (28th March 2022) - Bishop, Emma L.; Gudgeon, Nancy H.; Mackie, Gillian M.; Chauss, Daniel; Roberts, Jennie; Tennant, Daniel A.; Maslowski, Kendle M.; Afzali, Behdad; Hewison, Martin; Dimeloe, Sarah
Abstract: In CD4 + T helper cells, the active form of vitamin D3, 1, 25‐dihydroxyvitamin D3 (1, 25D) suppresses production of inflammatory cytokines, including interferon‐gamma (IFN‐γ), but the mechanisms for this are not yet fully defined. In innate immune cells, response to 1, 25D has been linked to metabolic reprogramming. It is unclear whether 1, 25D has similar effects on CD4 + T cells, although it is known that antigen stimulation of these cells promotes an anabolic metabolic phenotype, characterized by high rates of aerobic glycolysis to support clonal expansion and effector cytokine expression. Here, we performed in‐depth analysis of metabolic capacity and pathway usage, employing extracellular flux and stable isotope‐based tracing approaches, in CD4 + T cells treated with 1, 25D. We report that 1, 25D significantly decreases rates of aerobic glycolysis in activated CD4 + T cells, whilst exerting a lesser effect on mitochondrial glucose oxidation. This is associated with transcriptional repression of Myc, but not repression of mTOR activity under these conditions. Consistent with the modest effect of 1, 25D on mitochondrial activity, it also did not impact CD4 + T‐cell mitochondrial mass or membrane potential. Finally, we demonstrate that inhibition of aerobic glycolysis by 1, 25D substantially contributes to its immune‐regulatory capacity in CD4 + T cells, since the suppression of IFN‐γ expression was significantly blunted in the absence of aerobic glycolysis. 1, 25‐Dihydroxyvitamin D3 (1, 25D) suppresses the production of inflammatory cytokines such as interferon‐gamma (IFN‐γ) by CD4 + T cells, but the underpinning mechanisms are not yet fully defined. Here, we identify that 1, 25D inhibits aerobic glycolysis in activated CD4 + T cells, associated with decreased c‐Myc expression. This mechanism appears to substantially contribute to the suppression of IFN‐γ by 1, 25D, since this is significantly blunted in the absence of aerobic glycolysis. Abstract : 1, 25‐Dihydroxyvitamin D3 (1, 25D) suppresses the production of inflammatory cytokines such as interferon‐gamma (IFN‐γ) by CD4 + T cells, but the underpinning mechanisms are not yet fully defined. Here, we identify that 1, 25D inhibits aerobic glycolysis in activated CD4 + T cells, associated with decreased c‐Myc expression. This mechanism appears to substantially contribute to the suppression of IFN‐γ by 1, 25D, since this is significantly blunted in the absence of aerobic glycolysis.